Commercial Hormone Replacement Therapy Jeopardized Proinflammatory Factors in Experimental Rat Models - Ali, Mohammed; Mahmood, Isam H. (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: Hormonal contraceptive therapy is considered the easiest and most convenient contraceptive method. Commercially, available contraceptive combination differs in their composition and concentration of combined constituents. These variations make some of these products preferred over others by consumers based on their side effects profile. AIM: The objective of the current research was to ascertain the proinflammatory influences of commercially available products. METHODS: To do so, five groups of rats (ten rats in each group) were exposed to Microgynon, Depo-Provera, marvel on, and Yasmin compared to the control non-treated group. We measured proinflammatory markers including d-dimer, TNF-α (tumor necrosis factor-alpha), IL (interleukin)-6, IL (interleukin)-1B, and c-reactive protein. RESULTS: The results confirmed that Yasmin has induced the most deleterious effects on proinflammatory markers indicated by significant elevation of IL1B. CONCLUSION: Hormone replacement therapy should be critically indicated and precautions raised inpatient with subclinical diseases, especially cardiovascular ones.